Diagnostic value of cell bound and circulating neutrophil antibody detection in pediatric neutropenia. Issue 4 (12th December 2017) - Porretti, Laura; Farruggia, Piero; Colombo, Federico Simone; Cattaneo, Alessandra; Ghilardi, Roberta; Mirra, Nadia; Notarangelo, Lucia Dora; Martire, Baldassarre; Trombetta, Elena; Milani, Silvano; Vener, Claudia; Rebulla, Paolo
Abstract: Background: Chronic benign neutropenia of infancy includes primary autoimmune neutropenia (pAIN) and chronic idiopathic neutropenia (CIN). A diagnosis of CIN is supported by the absence of free and/or cell‐bound neutrophil autoantibodies, which can be detected by flow cytometry with the indirect‐granulocyte immunofluorescence test (I‐GIFT) and direct‐granulocyte immunofluorescence test (D‐GIFT), respectively. Conclusive evidence is lacking on the diagnostic value of the D‐GIFT, whose performance requires specific laboratory expertise, may be logistically difficult, and hampered by very low neutrophil count in patient samples. This study investigated whether the evaluation of D‐GIFT improves the diagnostic accuracy of pediatric neutropenia. Procedure: I‐GIFT and D‐GIFT were performed in 174 pAIN, 162 CIN, 81 secondary AIN, 51 postinfection neutropenic, and 65 nonautoimmune neutropenic children referred to this laboratory during 2002–2014. Results: Using 90% specific median fluorescence intensity cut‐off values calculated by receiver operating characteristic curves, D‐GIFT was positive in 49% of CIN patients, who showed similar clinical features as those with pAIN. In 44 (27%) of 162 CIN patients, I‐GIFT was repeated two to three times in a year, resulting positive in 12 and two patients at second and third screening, respectively. Interestingly, 10 of the latter 14 patients showed a positive D‐GIFT at the first serological screening. False positive D‐GIFT was shown by 12% and 22% of nonneutropenic and nonautoimmune neutropenic patients, respectively. Conclusions: D‐GIFT evaluation improves the diagnostic accuracy of pediatric neutropenia, but improvement of cell‐bound antibody detection is needed to decrease false positive results.